Digital beamforming implementation of switch-beam smart antenna system by using integrated digital signal processor and field-programmable gate array - Vakilian, Vida (2008)
Smart antenna technologies are emerging as an innovative way to meet the growing demand for more powerful, cost-effective and highly efficient wireless systems. If this system is implemented successfully, it could significantly improve the performance of wireless systems in terms of data rates, coverage and range. The best near-term application opportunities for smart antennas are wireless local area networks (WLANs), mobile DBS, WiMax, and cellular areas. The application targeted for this research is WiMax. Regardless of the application, hardware implementation of smart antenna is very challenging and complicated. Therefore, our focus is just on the beamforming and sidelobe cancellation for the WiMax downlink transmission. In downlink, we try to form and steer the beam according to the user location. Also, for more antenna radiation pattern optimization, the sidelobe cancellation is performed base on the chebyshev algorithm. In this respect, the system is firstly modeled by MATLAB software. After modeling, the algorithm is implemented in DSP. By using the Hardware- In-Loop facility of DSP, the comparison between hardware implementation and software modeling is performed. The results indicate that the digital beamforming and sidelobe cancellation are successfully implemented. At the next stage of the project, the signal management should be done before transmission to the expansion board. This management is necessary, in order to make data suitable for expansion board. After signal management the channels need to be split into sixteen antenna array elements by a means of FPGA board. To do so, the verilog code is written for programming the FPGA base on the signal which is come from DSP. The simulation results and measurement show that channels separation and synchronization is done successfully. By doing abovementioned procedure, the digital beamforming and sidelobe cancellation are implemented in baseband frequency.